Democracy, constitutional framework, and human rights: A comparison of Monaco, Tonga, Hong Kong, and Singapore - Wong, Mathew Y. H. (International journal of law, crime and justice, 2021)
This article examines constitutional protection of human rights, in particular civil liberties and political rights, in two democratic and two undemocratic regimes respectively. While the existing literature is consensual on the importance of constitutional democracy in upholding fundamental human rights, the discussion on authoritarianism is limited. This paper provides a comparative framework and suggests that not only do the constitutional democracies, namely Tonga and Monaco, perform well on constitutional human rights protection, Hong Kong and Singapore, both undemocratic, also demonstrate a similar level of protection on paper. Combining with their performance on human rights protection, it is argued that constitutional provisions in both democratic and authoritarian states carry limited significance, but how constitutions are interpreted and implemented matter the most.